2021
DOI: 10.3389/fpsyg.2021.600533
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Divergent Thinking Training on Teenagers’ Emotion and Self-Efficacy During the COVID-19 Pandemic

Abstract: Currently due to the COVID-19 pandemic, young people are experiencing a decrease in self-efficacy and an increase in mental illness. Though previous studies have shown that self-efficacy and divergent thinking training are positively related, little is known about the impact of divergent thinking training on self-efficacy and emotions. Therefore, our study seeks this answer to support teenagers injured psychologically during disastrous periods. We randomly assigned 70 students to a 2 (time: pretest, post-test)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 47 publications
0
17
0
5
Order By: Relevance
“…On the other hand, it would be interesting to conduct a correlational study of teachers’ perceptions of the impact of the use of facemasks on children’s literacy learning and emotional life, in order to check whether teachers establish some kind of dependence between both areas, as the literature points out [ 7 , 18 , 25 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it would be interesting to conduct a correlational study of teachers’ perceptions of the impact of the use of facemasks on children’s literacy learning and emotional life, in order to check whether teachers establish some kind of dependence between both areas, as the literature points out [ 7 , 18 , 25 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that facemasks have made it difficult for children to express feelings of disgust and have made them more prone to anxiety and fear [ 29 ], an effect that is particularly intense in children in early childhood education [ 30 ]. In adolescents, an increase in anxiety derived from the use of masks has been observed [ 31 ]. As for preschool, there are studies that explore the impact of the COVID-19 pandemic on early childhood education, but they are usually focused on describing the effects of the migration of education to virtual environments [ 32 , 33 ], or in exposing the experience teachers have had and the impact of the pandemic at the occupational level [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research by Garrod, Marshall, dan Jones shows that selfefficacy is essential in individual decisions to take preventive action against the disease (33). Selfefficacy and prevention practices are important in preventing COVID-19 in adolescents because self-efficacy plays a positive role for adolescents during the COVID-19 pandemic in maintaining optimism and mental health (21). Another study reported that perceived self-efficacy has a positive and significant correlation to cues to action (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adolescents have low self-efficacy because when faced with problems, they have fewer coping strategies compared to adults, as is the case during the current COVID-19 pandemic; therefore, it is essential to support adolescents during difficult times and build their mental health so as not to be disturbed (1,21). A preliminary study found high rates of depression (23 %), anxiety (19 %), and (52 %) experiencing moderate levels of worry (22).…”
Section: Covid-19 Remain a Global Threat That Causes Mortality And Mo...mentioning
confidence: 99%
“…In the COVID-19 pandemic, self-efficacy was associated with positive outcomes [10]. Even though self-efficacy plays a positive role in managing stressful events, these events can also undermine self-efficacy [11]. According to Alexander and Ward, people dealing with disasters have low coping abilities and physiological responses such as sweat and pain, which reduces self-efficacy [12].…”
Section: Introductionmentioning
confidence: 99%